The The Influence Of Service Quality, Brand Equity, Dan Price On Purchase Quality At Starbucks Outlets In Sidoarjo - Aqhillah Maulitha Kisbiyah; Misti Hariasih; Dewi Komala Sari (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study is aimed at examining the influence of service quality, brand equity, and pricing on consumer purchasing behavior at Starbucks outlets in Sidoarjo. Service quality stands as a pivotal determinant affecting customer buying choices, as evidenced by prior research highlighting the positive impact of superior service elements such as promptness, cleanliness, order accuracy, and staff affability on customer satisfaction. Hence, within the setting of Starbucks outlets in Sidoarjo, it is anticipated that high service quality will positively affect customer purchasing decisions. In addition to service quality, brand equity plays a critical role in shaping consumer purchase preferences. Starbucks has built a global reputation as a brand synonymous with top-tier product quality and a distinctive coffee shop experience. Previous studies have revealed that customers with favorable brand perceptions tend to exhibit a preference for products associated with such brands. Consequently, a robust brand equity at Starbucks Sidoarjo is anticipated to wield a positive influence on customer purchasing choices. Moreover, pricing has been identified as a significant determinant impacting purchasing decisions. Customers typically evaluate the price of Starbucks products in relation to their perceived quality and anticipated value from the brand. Prices deemed reasonable and commensurate with the overall brand experience are likely to sway customers’ decisions at Starbucks Sidoarjo outlets. As a result, this investigation concludes that service quality, brand equity, and pricing collectively wield substantial influence on purchasing decisions at Starbucks Sidoarjo outlets. Optimal service quality, strong brand equity, and appropriate pricing strategies have the potential to bolster customer satisfaction and shape their decisions to purchase Starbucks products.